Business Model Development Strategy for Ulee Kareeng Coffee Shop Based on Consumer Behaviour - Reza Muhammad Rifqi; Hartoyo Hartoyo; Mochammad Mukti Ali (Dinasti Publisher, 2025)
This research examines the business strategy transformation of Kedai Kopi Ulee Kareng & Gayo II, a traditional Acehnese coffee shop in Medan, in response to changing consumer preferences and competition from the modern coffee industry. Using the Business Model Canvas (BMC) approach, SWOT analysis, and consumer surveys, this study aims to identify the existing business model, analyze internal and external factors, and formulate new business strategies that are adaptive to market trends. The research methodology involves in-depth interviews with cafe management, distribution of questionnaires to 200 respondents, and comprehensive analysis of the nine BMC elements. The results indicate the need for strategic adjustments to reach millennial and Gen Z consumer segments while maintaining the cafe's traditional essence. Key findings yield ten strategic recommendations, including modernizing the cafe concept, optimising digital marketing, and diversifying partnerships. Managerial implications emphasize the importance of balancing innovation and preservation of traditional values in developing the new business model. This research contributes significantly to understanding the dynamics of traditional business adaptation in the digital era and provides a strategic framework for traditional coffee shop entrepreneurs to enhance competitiveness in an evolving market.